Upconversion rare Earths nanomaterials applied to photodynamic therapy and bioimaging - Rezende, Thaís K. L.; Barbosa, Helliomar P.; dos Santos, Luiz F.; de O. Lima, Karmel; Alves de Matos, Patrícia; Tsubone, Tayana M.; Gonçalves, Rogéria R.; Ferrari, Jefferson L. (Frontiers in Chemistry, 2022)
Light-based therapies and diagnoses including photodynamic therapy (PDT) and photodynamic diagnosis (PDD) have been used in many fields of medicine, including the treatment of non-oncological diseases and many types of cancer. PDD and PDT require a light source and a light-sensitive compound, called photosensitizer (PS), to detect and destroy cancer cells. After absorption of the photon, the PS molecule gets excited from its singlet ground state to a higher electronically excited state which, among several photophysical processes, can emit light and/or generate reactive oxygen species (ROS). Moreover, the biological responses are activated only in specific areas of the tissue that have been submitted to exposure to light. The success of the PDT depends on many parameters, such as deep light penetration on tissue, higher PS uptake by undesired cells as well as its photophysical and photochemical characteristics. One of the challenges of PDD and PDT is the depth of penetration of light into biological tissues. Because photon absorption and scattering occur simultaneously, these processes depend on the light wavelength. Using PS that absorbs photons on “optical transparency windows” of biological tissues promises deeper penetration and less attenuation during the irradiation process. The traditional PS is excited by a higher energy photon which has become the Achilles' heel in photodiagnosis and phototreatment of deep-seated tumors below the skin. Thus, the need to have an effective upconverter sensitizer is the property in which it absorbs light in the near-infrared (NIR) and emits in the visible and NIR spectral regions. The red emission can contribute to the therapy and the green and NIR emission to obtain the image. The absorption of NIR light by the material is interesting because it allows greater penetration depth for in vivo bioimaging and can efficiently suppress autofluorescence and light scattering. Consequently, the penetration of NIR radiation is greater, activating the biophotoluminescent material within the cell. Thus, materials containing Rare Earth (RE) elements have an advantage for these applications due to their attractive optical properties, such as several possibilities of excitation wavelengths , strong photoluminescence emissions, relatively long luminescence decay lifetimes, and high sensitivity and easy preparation.